2012
DOI: 10.1128/jvi.00051-12
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Is an Attachment Factor for Foamy Virus Entry

Abstract: The cellular receptor of foamy viruses (FVs) is unknown. The broad spectrum of permissive cells suggests that the cellular receptor is a molecular structure with almost ubiquitous prevalence. Here, we investigated the ability of heparan sulfate (HS), a glycosaminoglycan (GAG) present on the extracellular matrix of many cells, to bind FV particles and to permit prototype FV (PFV) and feline FV (FFV) entry. Permissivity of different cell lines for FV entry correlated with the amount of heparan sulfate pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 53 publications
8
44
0
1
Order By: Relevance
“…Interestingly, when we tested several other human cell lines we found that all FV tested showed varying abilities to replicate, and in some instances they were unable to replicate at all. Given that the proteoglycan heparin sulfate is known to be an important factor for FV attachment and entry, it is presumed that almost all human cells are permissive for FV entry (53). Our results provide indirect evidence that there are likely host factors involved in either supporting or inhibiting FV replication in humans.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, when we tested several other human cell lines we found that all FV tested showed varying abilities to replicate, and in some instances they were unable to replicate at all. Given that the proteoglycan heparin sulfate is known to be an important factor for FV attachment and entry, it is presumed that almost all human cells are permissive for FV entry (53). Our results provide indirect evidence that there are likely host factors involved in either supporting or inhibiting FV replication in humans.…”
Section: Discussionsupporting
confidence: 56%
“…SFV uses heparin sulfate to attach to target cells (47,48), but the receptor for SFV is still unknown (64). Interference studies showed that one cellular receptor is used by all SFVs (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
“…The broad tropism of SFV suggests a ubiquitous cellular receptor (42,43). While all SFVs seem to use the same cellular receptor (44)(45)(46), only heparin sulfate has been identified as an attachment factor so far (47,48).…”
mentioning
confidence: 99%
“…The FV Env trimers thereby appear to cluster into metastable hexamers with a central depression, thus giving the characteristic prominent extracellular spike structures observed on electron micrographs of FV particles [5]. Currently it is unknown whether this hexameric organization of the FV Env glycoprotein complexes is essential for host cell receptor recognition, as cellular attachment and entry factors are poorly characterized and non-permissive cells were only recently identified [6,7,8]. The first part of this review will focus on our current knowledge of molecular determinants of initial virus-host interactions that allow for FV attachment and glycoprotein-dependent release of capsids into the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%